The Protective Effect of Topical Spermidine on Dry Eye Disease with Retinal Damage Induced by Diesel Particulate Matter2.5 - Hyesook Lee; Da Hye Kim; Hyun Hwangbo; So Young Kim; Seon Yeong Ji; Min Yeong Kim; Jung-Hyun Shim; Sun-Hee Leem; Jin Won Hyun; Gi-Young Kim; Yung Hyun Choi (MDPI AG, 2021)
Air pollutants, especially ambient fine particulate matter2.5, may contribute to various ocular surface disorders, including dry eye disease, keratitis and conjunctivitis. A natural polyamine spermidine has a protective effect on the retina and optic nerve; however, no study has been conducted on the application of spermidine in particulate matter2.5-induced dry eye disease. In the present study, we investigated the effect of spermidine eye drops in topically exposed particulate matter2.5-induced dry eye models of Sprague-Dawley rats, by hematological, biochemical and histological evaluation. Spermidine eye drops attenuated the particulate matter2.5 exposure-induced reduction of tear secretion and corneal epithelial damage. Furthermore, spermidine protected against conjunctival goblet cell loss and retinal ganglion cell loss induced by particulate matter2.5. Additionally, spermidine markedly prevented particulate matter2.5-induced infiltration of cluster of differentiation3+ and cluster of differentiation4+ T lymphocytes and F4/80+ macrophages on lacrimal gland. Moreover, over expression of pro-inflammatory cytokines, including tumor necrosis factor-α, interleukin-6 and interleukin-17 in the lacrimal gland and cornea. Meanwhile, the levels of serum total cholesterol and low-density lipoprotein cholesterol were markedly increased by topical exposure to particulate matter2.5, but this change in the lipid profile was decreased by spermidine. Taken together, spermidine may have protective effects against particulate matter2.5-induced dry eye symptoms via stabilization of the tear film and suppression of inflammation and may in part contribute to improving retinal function and lipid metabolism disorder.